PENERAPAN SISTEM INFORMASI MANAJEMEN ANALISIS KELEMBAGAAN KABUPATEN CIANJUR DALAM MENINGKATKAN KINERJA BKPSDM KABUPATEN CIANJUR - Danny Permana (Jurnal Academia Praja, 2024)
This research aims to analyze the application of the Cianjur Regency Institutional Analysis Management Information System (Sianjab Manjur) in improving the performance of the Cianjur Regency BKPSDM, with a focus on the implementation of Sianjab Manjur as well as the supporting factors and obstacles faced and the efforts made by the Cianjur Regency BKPSDM in overcoming obstacles. the. The research methods used include interviews, secondary data collection, and data analysis. The research results show that although Sianjab Manjur has had a positive impact in improving the performance of BKPSDM Cianjur Regency, there are several challenges that need to be faced in its implementation. The first challenge is related to data security. As an information system that stores sensitive data regarding personnel, Sianjab Manjur must be able to maintain data security properly so that it is not misused by unauthorized parties. The second challenge is related to employee acceptance and adaptation to new information systems. Using Sianjab Manjur requires acceptance and adaptation from employees, especially those who are used to manual systems. BKPSDM needs to increase outreach and training efforts to employees so that they can master and use Sianjab Manjur well.